KOBIETY I MĘŻCZYŹNI O WARUNKACH ŻYCIA W BLOKACH - Janiszewska, Anna; Klima, Ewa; Rochmińska, Agnieszka (Space – Society – Economy, 2012)
The aim of the paper was to assess how citizens of Łód tower block housing estates evaluate their living conditions. The inner as well as outer housing space were analysed. Gender was treated as the main determining factor. It occurred that femininity or masculinity affected opinions in the very limited range. However one can point several elements which were perceived differently by men and women i.e. accessibility of recreation and leisure areas, accessibility of educational and health institutions. Respondents, regardless to their sex, evaluated their living space relatively high. The worse notes were given to “security”. The sense of security declared by respondents differed when considered their neighbourhood. The blocks dwellers felt most safe in their flats, less on the corridors in front of their doors and in front of their blocks but the least in places such as attics or cellars. It was no significant correlation between sense of security and gender although one can say that men were more “brave”. In conclusion it has to be stated once again that gender and sex were not key determiners in evaluation of respondents’ living space and conditions.